Chitosan‐heparin polyelectrolyte multilayers on cortical bone: Periosteum‐mimetic, cytophilic, antibacterial coatings. Issue 2 (1st September 2012) - Almodóvar, Jorge; Mower, Justin; Banerjee, Apurba; Sarkar, Ajoy K.; Ehrhart, Nicole P.; Kipper, Matt J.
Abstract: Cortical bone allografts suffer from high rates of failure due to poor integration with host tissue, leading to non‐union, fracture, and infection following secondary procedures. Here, we report a method for modifying the surfaces of cortical bone with coatings that have biological functions that may help overcome these challenges. These chitosan‐heparin coatings promote mesenchymal stem cell attachment and have significant antibacterial activity against both S. aureus and E. coli . Furthermore, their chemistry is similar to coatings we have reported on previously, which effectively stabilize and deliver heparin‐binding growth factors. These coatings have potential as synthetic periosteum for improving bone allograft outcomes. Biotechnol. Bioeng. 2013; 110: 609–618. © 2012 Wiley Periodicals, Inc. Abstract : The surface of devitalized cortical bone is modified with chitosan‐heparin polyelectrolyte multilayers. These biomimetic periosteum coatings are characterized spectroscopically, and shown to support the adhesion and proliferation of mesenchymal stem cells, while suppressing both Gram positive (S. aureus) and Gram negative (E. coli) bacteria. These coatings have potential as synthetic periosteum to improve the outcomes of cortical bone allografts.